Effect of a Mesoscale Eddy on Surface Turbulence at the Kuroshio Front in the East China Sea. Issue 3 (18th March 2019) - Yang, Guang‐Bing; Zheng, Quanan; Yuan, Yeli; Zhuang, Zhanpeng; Hui, Zhenli; Guo, Yan‐Liang; Yu, Long; Sun, Jia; Ju, Xia; Ma, De‐Jing; Hu, Xiaomin
Abstract: Field observations were conducted along three west‐east transects in the East China Sea Kuroshio Front in July 2017. The microstructure observations results show that the surface turbulence kinetic energy (TKE) dissipation rates in the northern and southern transects are about 2 orders larger than those in the middle transect. The sea surface temperature, mixed layer depth, and the submesoscale motions (with horizontal scales smaller than 30 km) also suggest the surface turbulences are more active in the northern and southern transects. The current velocity data and sea level anomaly show that the middle transect was located at the northern edge of a cyclonic eddy. The eddy‐generated cross‐front geostrophic current was observed to flow toward the opposite direction of the cross‐front Ekman transport and believed to counteract the Ekman buoyancy flux (EBF)‐induced turbulence enhancement. The TKE dissipation rates can be well scaled by a scaling considering the EBF and the wind in the northern and southern transects but wind scaling only in the middle transect, suggesting the EBF does not contribute to the surface turbulence in the middle transect. An improved empirical scaling considering the cross‐front geostrophic current is defined and can scale the TKE dissipation rates better, indicating an eddy plays a key role in surface turbulent mixing in the East China Sea Kuroshio front. Plain Language Summary: Ocean surface boundary layer is an important mediator for air‐sea interaction. Recent field observations have shown that the turbulence mixing within the ocean surface boundary layer can be significantly elevated at the front when the cross‐front Ekman transport carries dense cold water over less dense warm water. Our observations show that the mesoscale eddy also plays an important role in the surface turbulence at the front by generating cross‐front geostrophic current. This result may have important implications on the ocean model and climate forecast. Key Points: Expected Ekman buoyancy flux‐induced surface turbulence enhancement was not observed in the Kuroshio Front Eddy‐generated cross‐front geostrophic current counteracted the Ekman buoyancy flux‐induced surface turbulence enhancement Newly defined empirical scaling considering geostrophic current can better scale observed turbulent dissipation rates